Study of Literature: Implementation of Modeling Techniques Information Services to Increase Student Readiness for Vocational School Students for Practice - Ice Desvikayati; Firman; Netrawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Students' readiness to face Industrial Work Practices (Prakerin) is one indicator of the success of Vocational Schools in carrying out their functions. This research investigates the effectiveness of modeling engineering information services in increasing the readiness of Vocational High School (SMK) students to face Industrial Work Practices (Prakerin). This research method uses a literature study approach to prepare in-depth reviews of various articles and journals that are relevant to this topic. The results of the analysis show that modeling techniques significantly improve students' understanding of the world of work, help them develop practical skills such as communication and time management, and strengthen their confidence in facing challenges in the workplace. In addition, this technique also helps students identify and overcome potential obstacles they may face during internship, as well as prepare them to adapt to different work cultures. The implication of this study is the importance of integrating modeling techniques in the vocational education curriculum to prepare the younger generation to face the dynamic and competitive world of work.